人體器官買賣有何不可？: What is Wrong with the Buying and Selling of Human Organs? - YU, Kam Por (International Journal of Chinese & Comparative Philosophy of Medicine, 2001)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 本文檢討贊成和反對器官買賣的論據，討論了五個反對和兩個贊成器官買賣的論據。五個反對器宮買賣的論據是：（一）器官買賣剝削窮人；（二）器官買賣促進罪惡；（三）器官買賣製造家庭矛盾；（四）器官買賣鼓吹金錢萬能；（五）器官買賣貶低人性尊嚴。兩個贊成器官買賣的論據是：（一）買賣器官是個人權利；（二）買賣器官令資源得到更有效運用。筆者認為兩方面的論據都缺乏說服力，器官買賣並不是一個是非分明的問題，而是一個有待深思的倫理學難題。容許器官買賣，並不是等於完全容許自由買賣。在特定的限制下，例如：（一）限制買賣的類別；（二）限制賣方的資格；（三）限制買方的資格；（四）限制售賣的價格；（五）限制售貴的方式，可以將容許器官買賣的好處提高，及將容許器官買賣的壞處減低。在特定的情況下容許買賣，可以給予人們金錢利益以提高其供應器官的意顧，並不可以與完全自由買賣器官混為一談，值得進一步的認真探究。 ln this paper I examine the arguments for and against the buying and selling of human organs . I examine five opposing and two supporting arguments. The five opposing arguments are: (I) exploitation of the poor; (2) fostering crime; (3) creating a conflict between a person and his family; (4) contributing to the prevailing ethos of everything being for sale; (5) degrading human dignity. The two supporting arguments are: (1) self-ownership of human beings; (2) effective use of resources. I argue that none of the opposing and supporting arguments are convincing. The buying and selling of human organs is not a problem with a clear and easy answer. It is instead a difficult ethical problem. The use of the profit incentives to increase the supply of organs should not be mixed up with a literal commodification of human organs. There can be different ways of selling organs. Although human organs may have a special status quite different from other commodities, this may just mean that human organs should be sold very differently rather than that they should not be sold at all. Organ selling can be restricted in the following ways: (1) buyer, e.g. only the government can be the buyer; (2) seller, e.g. only the "host" can be the seller (i.e. no resale is allowed); (3) price, e.g. one price system; (4) form, e.g. financial gain but no cash payment (such as reduction of insurance premium or compensation of estate); (5) content, e.g. only cadaveric organs can be sold; (6) purpose, e.g. only for transplantation. Under such or similar restrictions, the advantages of allowing buying and selling organs can be promoted and the disadvantages can be avoided. Such arrangements deserve further investigation. If we take such restrictions into consideration, many objections against organ selling are not as convincing as they first appear to be. My conclusions are as follows: (I) The arguments against the selling of organs as outlined in this paper can at most show that an unrestricted free market of organs is wrong, but they cannot show that the use of monetary incentives to increase the supply of organs is wrong. (2) The arguments for the selling of organs as outlined in this paper cannot show that people have a right to sell their organs. (3) It does not seem unreasonable to hold the view that the use of monetary incentives is acceptable but an unrestricted free market of human organs is not. DOWNLOAD HISTORY | This article has been downloaded 1039 times in Digital Commons before migrating into this platform.